Hepatoprotektor Rumput Laut Eucheuma cottonii Pada Tikus Putih (Rattus norvegicus L.) Jantan Yang Diinduksi Natrium Nitrit (Nano2) - Ida Ayu Ratih Purnama Dewi; Ngurah Intan Wiratmini; Iriani Setyawati (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2020)
Sodium nitrite (NaNO2) is a food preservative that is often added to processed meat products. Excessive consumption of NaNO2 can be detrimental to health. One effort to minimize the negative effects caused by NaNO2 is by consuming antioxidants. This study aimed to determine the effectiveness of Eucheuma cotonii seaweed extract on improving blood profile, liver and kidney function in male white rats (Rattus norvegicus) induced by NaNO2. This research used a Completely Randomized Design (CRD) consisting of two control groups and three treatment groups. Each group consists of six replications. Negative control (K-) receive aquades and CMC NA 0,5%. Positive control (K +) was only received 22.5 mg/kgBW NaNO2 for 35 days then on the day 36 until the day 45 only given 0,5% CMC Na. The treatment groups P1, P2, and P3 respectively on day 1 to day 15, only received 22.5 mg/kgBW NaNO2 in the morning, and then day 16 to day 35 received 22.5 mg/kgBW NaNO2 in the morning and received 150 mg/kgBW (P1), 300 mg/kgBW (P2), 450 mg/kgBW (P3) Eucheuma cottoni seaweed extract in the evening. Day 30 to day 45, the treatment groups only received Eucheuma cottoni seaweed extracts at each dose. Blood and liver were collected on day 46. Data analysis of serum alanine transaminase (ALT) and aspartate aminotransferase (AST) enzyme levels and liver histology were performed with Anova statistical test and continued with Duncan post hoc test. The results showed Eucheuma cottonii extract dose of 150 mg / kgBB significantly reduced the level of liver damage seen from the levels of ALT and AST and liver histology (percentage inflammatory cell infiltration, congestion, fatty degeneration and necrosis) in white rats induced by sodium nitrite (NaNO2). Keywords: Preservative, AST, ALT, histopathology, liver